The role of shadow banking in systemic risk in the European financial system - Bellavite Pellegrini, Carlo; Cincinelli, Peter; Meoli, Michele; Urga, Giovanni (Journal of Banking & Finance, 2022)
We study how the characteristics of different financial institutions relate to systemic risk using the ΔCoVaR measure of Adrian and Brunnermeier (2016). We contrast traditional banks with shadow entities, such as Money Market Funds and Finance Services, using a sample of 476 European financial institutions between 2006 and 2015. We find that systemic risk increases significantly in the size of large financial institutions, particularly Money Market Funds, while it is insensitive to the size of Finance Services. We also find that Finance Services are particularly sensitive to proxies for market risk. For traditional banks, their reliance on short term wholesale funding is a key determinant of their contribution to systemic risk.